Determinanty rozwoju gospodarczego gmin w Poznańskiem - Bak, Urszula (Wydział Prawa i Administracji UAM, 1992)
The author distinguished three major factors responsible for civilizational transformations in the communes of Poznań Province: the level of actual living conditions, the degree of productive activity of households, and the level of technical equipment of households. The analysis has led the author to the following generalizations: (1) civilizational transformations were the least intensive in the agricultural regions; (2) the highest level of civilizational transformations was found in communes located near Poznań and in t h e communes which previously housed local administration °f medium level (abolished in 1975); and (3) the level of technical equipment of households in the Poznań Province was usually higher t h an the level to which the productive activity in agriculture would indicate.
Determinants of economic growth of communes in the Poznań province